2014
DOI: 10.1177/0021998314533597
|View full text |Cite
|
Sign up to set email alerts
|

Core-thickness effect on the impact response of sandwich composites with poly(vinyl chloride) and poly(ethylene terephthalate) foam cores

Abstract: The objective of this study was to investigate the effects of core material and its thickness on impact behavior of sandwich composite plates subjected to low-velocity impact, experimentally. Poly(vinyl chloride) (PVC) and poly(ethylene terephthalate) (PET) foams were selected as the core material, having approximate density of 65 kg/m3 and 60 kg/m3, respectively, and thicknesses of 5, 10, and 15 mm. The stacking sequence of the sandwich composites is [Formula: see text] Impact tests were carried out by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 17 publications
2
31
0
5
Order By: Relevance
“…The longer plateau results in higher energy absorption as seen in Fig 12 (c) and was related to the interaction of the impactor through the relatively thicker foam core in H25 compared to H15 specimens for the perforation case. Such results have been observed in previous studies [47,48]. The authors reported that with increasing the core thickness, the penetration can occur at a wider energy range under LVI loadings [48].…”
Section: Single Foam Core Sandwich (Sfs) Design With Ashwood Skinsupporting
confidence: 86%
See 1 more Smart Citation
“…The longer plateau results in higher energy absorption as seen in Fig 12 (c) and was related to the interaction of the impactor through the relatively thicker foam core in H25 compared to H15 specimens for the perforation case. Such results have been observed in previous studies [47,48]. The authors reported that with increasing the core thickness, the penetration can occur at a wider energy range under LVI loadings [48].…”
Section: Single Foam Core Sandwich (Sfs) Design With Ashwood Skinsupporting
confidence: 86%
“…Such results have been observed in previous studies [47,48]. The authors reported that with increasing the core thickness, the penetration can occur at a wider energy range under LVI loadings [48]. Also, it was observed that as the core thickness increased, specimens showed more elastic behaviour and so, the maximum contact force decreased while contact time and maximum deflection values were increasing.…”
Section: Single Foam Core Sandwich (Sfs) Design With Ashwood Skinsupporting
confidence: 84%
“…Zhou ve arkadaşları [14] farklı türden polimer köpükler ile üretilen sandviç panelleri düşük hız darbe testine tabi tutmuş ve batma direncinin köpük türüyle ilişkili olduğunu güçlü bir şekilde ortaya koymuşlardır. Özdemir ve arkadaşları [15] iki farklı PVC ve PET köpük malzemeyi çekirdek malzeme olarak kullanarak bunların farklı kalınlıklardaki etkilerini incelemiştir.…”
Section: öNceki̇ çAlişmalarunclassified
“…The material of the facesheet was Aluminium 2024-T3, and the core materials were Balsa wood of low density (LD) and high density (HD), Cork, Polypropylene (PP) honeycomb, and Polystyrene (PS) foam. It was found that the core height has a significant influence on the impact response of sandwich structures [7,16,25,26], so the thicknesses of cores were kept nominally constant to eliminate the geometry effect on the bending stiffness, leaving only the effect of the material properties of the core as the variable. Table 1 summarises the properties of all the materials used: the thickness and density were measured directly while the Young's modulus, compressive strength, and shear strength were obtained from the manufacturer's data and published literature [27,28].…”
Section: Materials Usedmentioning
confidence: 99%
“…The effects of impact variables (such as impact velocity and energy, impactor shape and diameter) and sandwich construction parameters (core material and thickness, facesheet type) on the impact behaviour and resulting damage are the major concerns in many studies. According to Ozdemir et al [7], the core material and thickness is one of the main factors determining the impact behaviour of sandwich structures and it was shown that the energy absorption capacity of sandwich composites increased with increasing core thickness.…”
Section: Introductionmentioning
confidence: 99%